2009
DOI: 10.2118/92868-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grid Deviation on Flow Solutions

Abstract: The two-point flux finite-volume method (2P-FVM) is the most widely used method for solving the flow equation in reservoir simulations. For 2P-FVM to be consistent, the simulation grid needs to be orthogonal (or k-orthogonal if the permeability field is anisotropic). It is well known that corner-point grids can introduce large errors in the flow solutions because of the lack of orthogonality in general. Multipoint flux formulations that do not rely on grid orthogonality have been proposed, but these methods ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Around the border, PEBI grids lose the feature of orthogonality to radial grids. This would cause unnecessary numerical errors [9]. Our method can avoid these flaws and make better grids.…”
Section: A Arrange Grid Points In Vertical Well Dominant Areamentioning
confidence: 99%
“…Around the border, PEBI grids lose the feature of orthogonality to radial grids. This would cause unnecessary numerical errors [9]. Our method can avoid these flaws and make better grids.…”
Section: A Arrange Grid Points In Vertical Well Dominant Areamentioning
confidence: 99%
“…Such a gridding strategy usually requires significant simplifications in the fault description. In the subsequent gridding process, one is faced with two choices: The extrusion direction and the cell faces in the grid can be set to follow major fault surfaces, which gives grid cells that are not Korthogonal and hence susceptible to large discretization errors when used together with a traditional two-point method [see Aavatsmark (2007) and Wu and Parashkevov (2009)]. These discretization errors can be reduced by using a more-accurate discretization.…”
Section: Introductionmentioning
confidence: 99%
“…This will create cells that are mostly K-orthogonal and hence limit the two-point discretization errors. Likewise, areal distortions can be reduced by using 2.5D Voronoi grids (Wu and Parashkevov 2009;Branets et al 2009). Another alternative is to use unstructured grids to adapt to complex fault networks (Gringarten et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, K-orthogonality is often lost in the grids that honor the geologic features such as the sloping faults and channels, and other important features such as nearly horizontal wells [18]. Recently, Wu and Parashkevov studied the effect of non-orthogonality error of deviated grids on the flow solutions from the two-point flux, control volume method [35]. They concluded that for most practical cases the errors in horizontal flow are relatively small and the errors in vertical flow can be rather significant.…”
Section: Introductionmentioning
confidence: 99%